Planning of Solar Power Plant SMA LabSchool UPGRIS with PV*SOL - Kusmantoro, Adhi - (Journal of Electrical Engineering and Computer (JEECOM), 2025)
The increase in the use of electrical energy is increasing in the development of technology at this time. At present in Indonesia, power plants still use non-renewable energy sources that will eventually run out. The purpose of this study is to provide a source of electricity with solar energy sources, so that dependence on PLN electricity can be reduced. The method used is planning and simulating using PV*SOL software. The planned location for the installation of Solar Power Plant (SPP) is in the Gayamsari District, Semarang City, Central Java. The location of the SMA Building has an area of 1773 m2 with coordinates of Latitude -6.9830564° N, 110.4494686 ° E. In the planning, the stages are determining the location of the PLTS, identifying solar radiation intensity data, identifying electrical load data, determining solar panel capacity, determining battery capacity, determining inverter capacity, and determining the capacity of the Solar Charge Controller (SCC). The planned SPP operates in an off-grid system. In carrying out this planning with stages. The results of the study showed that the amount of daily electricity consumption was 18,402 Wh and the electricity consumption for one month was 552,060 Wh. The simulation showed that solar panels effectively produced an average of 1300 kWh of electricity. The production of large solar panels occurred from April to October, with an average energy of 130 kWh. The results of the study showed that the amount of electricity consumption was large but could be served by solar power plants.